Impact of Granulocyte Colony-Stimulating Factor (G-CSF) on Clinical Outcomes in Allogeneic Hematopoietic Cell Transplantation: Does Speeding Up Neutrophil Engraftment Make a Difference? - Ahmed Alnughmush, MD; Ayman Sayyed, MD; Mats Remberger, PhD; Eshrak AL-Shaibani, MD; Carol Chen, BSc; Caden Chiarello; Ivan Pasic, MD; Igor Novitzky-Basso, MD; Arjun Datt Law, MD; Wilson Lam, MD; Dennis (Dong Hwan) Kim, MD; Armin Gerbitz, MD; et al. (Transplantation Direct)
Background. Despite decades of post–allogeneic hematopoietic cell transplantation (HCT) growth factor utilization, its role remains undefined, leading to ongoing debates and research. The theoretical impacts of growth factors have been challenged in numerous studies. Methods. In this retrospective cohort study conducted at the Princess Margaret Cancer Centre, we analyzed the clinical outcomes of 509 patients who underwent allogeneic HCT between May 1, 2019, and May 31, 2022. This study aimed to assess the impact of granulocyte colony-stimulating factor (G-CSF) administration posttransplantation on neutrophil and platelet engraftment, incidence of bloodstream infections (BSIs), graft-versus-host disease, engraftment syndrome (ES), and survival metrics including overall survival, nonrelapse mortality, and graft-versus-host disease–free/relapse-free survival. Results. Our findings indicate that G-CSF administration expedited neutrophil engraftment (16 versus 18 d, P = 0.009) and was associated with a decreased incidence of BSI (9.4% versus 31.3%, P = 0.014). However, this benefit was counterbalanced by a significant delay in platelet engraftment (21 versus 17 d, P < 0.001). Multivariate logistic regression analysis identified mismatched donors (odds ratio, 1.72; 95% confidence interval, 1.03-2.88; P = 0.038) and the duration of G-CSF therapy (odds ratio, 1.04; 95% confidence interval, 1.00-1.09; P = 0.038) as independent predictors for the development of ES. Despite these hematological impacts, there was no observed advantage in overall survival, nonrelapse mortality, or graft-versus-host disease–free/relapse-free survival among patients who received G-CSF compared with those who did not. Conclusions. Although G-CSF post-HCT expedited neutrophil engraftment and reduced BSI risk, it did not result in a survival advantage. The association with ES necessitates careful consideration.